1999
DOI: 10.1111/j.1530-0277.1999.tb04351.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcoholism Is Associated With an Imbalanced Production of Th‐1/Th‐2 Cytokines by Peripheral Blood T Cells

Abstract: Our results showed that in patients with chronic alcoholism, active EtOH intake is associated with a Th-1 pattern of cytokine production by PB T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 33 publications
(22 reference statements)
3
40
1
1
Order By: Relevance
“…Lifestyle factors such as physical activity, smoking and alcohol intake are known to influence the percentage of peripheral blood lymphocytes [3,9,10,13]. In our series, individuals who performed health-enhancing physical activity had a higher percentage of lymphocytes and DN cells and a lower percentage of CD4+ cells than minimally active or inactive individuals.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Lifestyle factors such as physical activity, smoking and alcohol intake are known to influence the percentage of peripheral blood lymphocytes [3,9,10,13]. In our series, individuals who performed health-enhancing physical activity had a higher percentage of lymphocytes and DN cells and a lower percentage of CD4+ cells than minimally active or inactive individuals.…”
Section: Discussionmentioning
confidence: 52%
“…Other determinants related to lifestyle can also affect lymphocyte subsets. These include physical activity [9], ethanol intake [10,11] and cigarette smoking [12]. The determination of lymphocyte subsets is also influenced by variations in the study design and analytical techniques and procedures [13].…”
Section: Introductionmentioning
confidence: 99%
“…13,19 These results suggest similar IL-6 responses to liver injury in alcoholic liver disease and obesity-related liver disease in both humans and mice. [9][10][11][12][13] The consequences of chronic IL-6 over-expression and persistent signaling in alcoholic and obesity-related hepatocyte dysfunction are unknown, and the existing data are conflicting. Although administration of IL-6 improved the regenerative response in obese Zucker rats, hyperstimulation with IL-6 administered to transgenic mice expressing soluble human IL-6R␣ actually repressed cell cycle progression after hepatectomy, suggesting that IL-6 can inhibit liver growth after injury.…”
mentioning
confidence: 99%
“…These reports suggest an important role of IL-6 in acute liver injury and a beneficial effect of IL-6 production in repetitive liver injury. [9][10][11][12][13] IL-6 is both pro-mitogenic and anti-apoptotic for hepatocytes. We have demonstrated that prolonged exposure to continuous, supraphysiological levels of IL-6 induces hepatocyte proliferation in vivo.…”
mentioning
confidence: 99%
“…response were associated with immune abnormalities (10)(11)(12)(13). Chronic alcoholism is associated also with numerical, phenotypical, and functional changes in circulating peripheral blood dendritic cells (DCs).…”
mentioning
confidence: 99%